PF.47 Routine Cervical Assessment at Anomaly Scan May Reduce Neonatal Morbidity and Mortality Associated with Preterm Birth. (26th April 2013) - Crosby, DA; Daly, S
Abstract : A recent metaanalysis has suggested that measurement of the cervical length should be performed in conjunction with the anomaly scan (1). We decided to investigate if this recommendation is justifiable in a population where the risk of preterm birth is low. Methods: We reviewed 11 years of obstetric data from the Coombe Women and Infants University Hospital. Relative risks of adverse outcomes from the metanalysis were applied and we extrapolated the possible numbers of women requiring intervention. Results: Over the 11 years from 1999 to 2010, there were 94, 646 singleton deliveries. There were 881 births (0.93%) as a result of spontaneous labour from 19–34 weeks, of which 805 were livebirths. Applying the figures from the metaanalysis 1609 women who had a singleton pregnancy could be expected to have a cervical measurement <15 mm. If none of these women received progesterone we could expect 515 women (32.1%) to deliver at <34 weeks. If we gave progesterone to all these women we would prevent 281 births at less than 34 weeks (17.5%). Therefore we would reduce the delivery rate before 34 weeks by 234 pregnancies, which is 21 babies a year. Conclusion: In units where the spontaneous preterm rate is low it is difficult to suggest that routine cervical measurement is justified. Each individual hospital should evaluate the possible benefits of universal screening for a short cervix prior to instigating a policy of performing a transvaginal ultrasound assessment of cervical length at the time of the anomaly scan. Reference: Romero et al. Vaginal progesterone in women with an asymptomatic sonographic short cervix in the midtrimester decreases preterm delivery and neonatal morbidity: a systematic review and metaanalysis of individual patient data. American Journal of Obstetrics & Gynecology 2012;206:e1-124.